BRAF inhibitor and stereotactic radiosurgery is associated with an increased risk of radiation necrosis. Issue 4 (August 2016) - Patel, Kirtesh R.; Chowdhary, Mudit; Switchenko, Jeffrey M.; Kudchadkar, Ragini; Lawson, David H.; Cassidy, Richard J.; Prabhu, Roshan S.; Khan, Mohammad K.
Abstract : We retrospectively compared the outcomes and toxicities of melanoma brain metastases (MBM) patients treated with BRAF inhibitors (BRAFi) and stereotactic radiosurgery (SRS) with SRS alone. We identified 87 patients with 157 MBM treated with SRS alone from 2005 to 2013. Of these, 15 (17.2%) patients with 32 MBM (21.4%) received BRAFi therapy: three (20.0%) before SRS, two (13.3%) concurrent, and 10 (66.7%) after SRS. Overall survival (OS) was compared between cohorts using the product limit method. Intracranial outcomes were compared using cumulative incidence with competing risk for death. Baseline patient characteristics were similar between groups, except for the SRS cohort, which had higher rates of chemotherapy and more recent year of diagnosis. Radiation characteristics, including dose per fraction, total dose, gross tumor volume size, and prescription isodose, were also similar between cohorts. One-year outcomes – OS (64.3 vs. 40.4%, P =0.205), local failure (3.3 vs. 9.6%, P =0.423), and distant intracranial failure (63.9 vs. 65.1%, P =0.450) were not statistically different between the SRS+BRAFi and SRS-alone groups, respectively. The SRS+BRAFi group showed higher rates of radiographic radiation necrosis (RN) (22.2 vs. 11.0% at 1 year, P <0.001) and symptomatic radiation necrosis (SRN) (28.2 vs. 11.1% at 1 year, P <0.001). Multivariable analysis showed that BRAFi predicted an increased risk of both radiographic and SRN. SRS and BRAFi predicted for an increased risk of radiographic and SRN compared with SRS alone. Approaches to mitigate RN for patients receiving SRS and BRAFi should be considered until the clinical trial (http//:www.clinicaltrials.gov : NCT01721603) evaluating this treatment regimen is completed.